Лізинг як джерело фінансування впровадження автоматизованої системи обліку оплати проїзду - Мельник, Т. А.; Melnyk, Т. (ЦНТУ, 2017)
В статті наводяться преваги використання автоматизованої системи обліку оплати проїзду, окреслюються основні елементи цієї системи, досліджуються різні джерела фінансування для закупівлі необхідного обладнання кліринговим центром та транспортними підприємствами, характеризуються різні підходи до фінансування лізингу. Запропоновано залучати страхові ресурси страховиків для фінансування лізингу в транспортній галузі, а також використовувати зворотній лізинг для закупки необхідного обладнання кліринговим центром та транспортними підприємствами. The purpose of the article is to substantiate the feasibility of using leasing operations as the most effective source of financing for transport enterprises, recommendations on the use of reverse leasing and attraction of technical (mathematical) reserves of insurance companies to finance implementation programs automated payment for fare system. This article lists preferences when using an automated payment for fare system for the population, local authorities and the state. This article lists the main elements of the automated payment for fare system. This article studied different sources of financing (lease, instalment, bank credit, leasing) for the purchase of necessary equipment for transport companies and clearing centre. This article characterized by different approaches (issue of shares, issue of bonds, banking factoring, bank credit) to the financing of the leasing. It is proposed to involve the insurance company resources to finance leasing in the transport sector. It is proposed to use a reverse leasing for the purchase of necessary equipment for clearing centre and transport enterprises.
Leasing as a source of funding for the implementation of an automated payment for fare system
Keywords: лізинг; автоматизована система обліку оплати проїзду; зворотній лізинг; джерела фінансування лізингу; розміщення страхових резервів страховиків; схема лізингу; фінансування транспорту; leasing; automated payment for fare system; leaseback; sources of finance leasing; placement of insurance reserves of insurers; leasing scheme; financing transport funding